Pengaruh Penggunaan Financial Technology (Fintech) Payment dan Uang Saku terhadap perilaku keuangan mahasiswa S1 Manajemen Fakultas Ekonomi dan Bisnis Angkatan 2019 Universitas Trunojoyo Madura - Hamro, Najmatul; Susandini, Aprilina (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of using financial technology (Fintech) Payments and Pocket Money on the financial behavior of S1 Management students at the Faculty of Economics and Business Class of 2019, University of Trunojoyo Madura. The population used in this study was 282 students with purposive sampling method and 165 students were selected as samples in this study. The method used is descriptive quantitative. The data used in the study were obtained by distributing questionnaires to 2019 Batch of Management students at the Faculty of Economics and Business University of Trunojoyo Madura. The results of this study indicate that financial technology (fintech) Payment has a positive and significant effect on the financial behavior of S1 Management students at the Faculty of Economics and Business Class of 2019 Trunojoyo University Madura, Pocket Money has a positive and significant effect on the financial behavior of S1 Management students at the Faculty of Economics and Business Class of 2019 University Trunojoyo Madura and financial technology (fintech Payment and Pocket Money) have a positive and significant effect on the financial behavior of S1 Management students at the Faculty of Economics and Business Class of 2019, University of Trunojoyo Madura.